2014
DOI: 10.1186/1757-2215-7-49
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative HE4 and ROMA values do not improve the CA125 diagnostic value for borderline tumors of the ovary (BOT) – a study of the TOC Consortium

Abstract: BackgroundBorderline tumors of the ovary (BOT) are a distinct entity of ovarian tumors, characterized by lack of stromal invasion. Recent studies postulated that the presence of invasive implants, incomplete staging, fertility sparing surgery and residual tumor after surgery are major prognostic factors for BOT. There are no biomarkers that can predict BOT or the presence of invasive implants.ObjectiveThe aim of our study was to assess the value of CA125 and HE4 alone, or within ROMA score for detecting BOT, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…A recent prospective study suggested that ROMA, and also HE4 alone, showed similar performance to CA125 alone in pre-menopausal women, but worse performance in postmenopausal women ( 22 ). In another retrospective study, HE4 was not superior to CA125 in predicting borderline ovarian tumors or presence of invasive implants ( 35 ).…”
Section: Discussionmentioning
confidence: 92%
“…A recent prospective study suggested that ROMA, and also HE4 alone, showed similar performance to CA125 alone in pre-menopausal women, but worse performance in postmenopausal women ( 22 ). In another retrospective study, HE4 was not superior to CA125 in predicting borderline ovarian tumors or presence of invasive implants ( 35 ).…”
Section: Discussionmentioning
confidence: 92%
“…Divergent results were reported by Braicu and his colleagues [69]. Studies on subjects covering 63 BOT patients and 104 patients with benign diseases of ovarian fibrothecoma and uterine leiomyomata found that serum HE4 was elevated only in postmenopausal BOT cases, but not in premenopausal BOT patients.…”
Section: Nonmalignant Cyst Of Ovarymentioning
confidence: 82%
“…The serum-based Risk of Malignancy Algorithm (ROMA) and OVA1 ™ tests also represent relatively new multimarker algorithms for the management of ovarian cancer. Although both tests have seen some success leading up to FDA-approval, there are still conflicting results as to how well they truly perform compared to CA125 [3034]. Furthermore, due to the fact that the algorithms rely heavily on serum levels of CA125 and/or HE4, they are susceptible to bias towards patients with late-stage cancers and/or serous carcinoma (most often high-grade serous carcinoma) [35].…”
Section: Discussionmentioning
confidence: 99%